Distribution of Human Immunodeficiency Virus Type 1 Protease and Reverse Transcriptase Mutation Patterns in 4,183 Persons Undergoing Genotypic Resistance Testing - Rhee, Soo-Yon (American Society for Microbiology, 2004)
In a sample of 6,156 sequences from 4,183 persons, the top 30 patterns of protease inhibitor, nucleoside reverse transcriptase (RT) inhibitor, and nonnucleoside RT inhibitor mutations accounted for 55, 46, and 66%, respectively, of sequences with drug resistance mutations. Characterization of the phenotypic and clinical significance of these common patterns may lead to improved treatment recommendations for a large proportion of patients for whom antiretroviral therapy is failing.